The Origin of Oxygen Vacancies Controlling La2/3Sr1/3MnO3 Electronic and Magnetic Properties. Issue 5 (8th January 2016) - Guo, Haizhong; Wang, Jia‐ou; He, Xu; Yang, Zhenzhong; Zhang, Qinghua; Jin, Kui‐juan; Ge, Chen; Zhao, Ruiqiang; Gu, Lin; Feng, Yaqing; Zhou, Wenjia; Li, Xiaolong; et al.
Abstract : Mixed‐valence manganites gain increasing attentions thanks to their extraordinary properties including half‐metallicity and colossal magnetoresistive response, rendering them ideal candidate for oxide spintronics applications. Oxygen vacancies in oxides have been approved to be important functional defects and are effective to manipulating their multifunctional properties. To gain a deep insight into the roles of oxygen vacancies on regulating the atomic structure and electronic properties of the mixed‐valence manganites, two high‐quality epitaxial La2/3 Sr1/3 MnO3 films around a critical point (without/with oxygen vacancies) were designed and fabricated. From the experiments and theoretical calculations, it was found that the oxygen vacancies induce a weakening of Mn–O–Mn hybridized bond and an increase of concentration of Mn 3+ ions, impair the double exchange between Mn 3+ and Mn 4+, and therefore lead to the transition from metal to insulator and the degraded magnetic properties. Our finding demonstrates a practical approach to tune the magnetic and transport properties of oxide thin films by precisely controlling the oxygen vacancies for high performance spintronics applications. Abstract : The La2/3 Sr1/3 MnO3 /SrTiO3 interface under high oxygen pressure is shown to be atomically sharp and coherent with scanning transmission electron microscopy. HL reciprocal space mapping shows a single peak structure. The strong enhancement of the Mn 3 d spectral intensity is observed. The density of states projected on the d 3z 2 − r 2 orbital is reduced.